Methicillin Resistant Staphylococcus aureus Isolated from Wound Infections (Tribhuvan University Journal of Microbiology, 2018)
Objectives: The aim of this study was to determine the prevalence of methicillin resistant Staphylococcus aureus (MRSA) and antibiotic resistance pattern of the isolates from wound infections.Methods: A total of 706 wound specimens including pus and wound swab were analyzed in the laboratory of B and B Hospital, Lalitpur from May to October 2014. The specimens were cultured on Blood Agar and Mannitol Salt Agar plates and incubated at 37°C for 24 hours. Antibiotic susceptibility test was performed by modified Kirby-Bauer disc diffusion method. Strains resistant to cefoxitin (30mcg) with inhibition zone ≤ 21mm were identified as MRSA.Results: Out of 366 bacterial isolates, 90 (24.6%) were S. aureus and among them 16.7% were MRSA and 54.4% multi-drug resistant (MDR). All isolates were sensitive to vancomycin and most of the isolates were sensitive to cefoxitin (83.3%). High rate of resistance was observed towards penicillin (98.9%) and ampicillin (86.7%). All MRSA isolates and 52.9% of methicillin sensitive S. aureus (MSSA) were MDR.Conclusion: MRSA incidence is increasing in the population, and therapeutic measures are few and accompanied by diverse side effects. It is noteworthy to state that vancomycin is still the first line drug although vancomycin-resistant strains have been reported.